Socioeconomic and behavioral factors associated with inequality in the obesity of men and women in Brazil - Pt, Pt; Pt, Pt; Pt, Pt (Estudos Econômicos (São Paulo), 2023)
The purpose of the research is to analyze socioeconomic inequality in the distribution of obesity, which is not only a disease, but also a social and economic phenomenon. In the article, the objective is to investigate the factors that make adult men and women have different probabilities of being obese in Brazil. Initially, obese individuals are identified using the Relative Fat Mass (RFM). Then, the Probit model is estimated, and Fairlie decomposition is subsequently applied. In general, the coefficients obtained are satisfactory and statistically significant. The main results indicate that women are more likely to be obese than men. The income, marital status, leisure-time physical activity, consumption of beans, alcoholic beverages and cigarettes have the greater relationship with gender inequality in obesity.